Curriculum by competencies seen from inclusive education: a challenge that responds to the factors of exclusion and social inequity - Osorio Galindo, Franklin Manuel (2021)
This article for reflection arises from the academic space of the competence development module through the didactic planning of the Doctorate in Educational Sciences of the Metropolitan University of Education, Science and Technology UMECIT (Panamá), which aims to visualize the contributions of the Competency-based approach to curriculum design, teaching practices, and forms of evaluation that take place in education. The methodology developed was qualitative-reflective, using bibliographic or documentary sources, the main findings are focusedon the explanation, conceptual position and importance of inclusive education as an inclusive educational model and how it responds to the challenges of exclusion and social inequity. It alsohighlights elements transformations of the school as an inclusive space, permeated in equity through the curriculum. By way of conclusion of this theoretical reflection, the strategies andcurricular redesigns that tend to the development of the competences and learning of the students are recognized, where everyone is included from a school environment. Not only withaccess is it attended to the inclusion requirements, it is also necessary to provide equity.